Analysis, modelling, and financial perspectives of reverse mortgage implementation in Colombia (2024)
Purpose: Increased life expectancy in recent years, together with the downward trend in fertility rates, will accelerate the aging of the Latin American population (Flamini and et al., 2018) [1]. This demographic change represents a problem for pension systems as the economic capacity to f inance the retirement of the population could be insufficient in the future. This creates a favorable scenario for new financial products, including reverse mortgages. This study determines, from the supply approach, the potential of reverse mortgages in the main cities of Colombia as a complement to the financing of old age according to the guidelines of Benavides et al. (Benavides Franco et al., Jan. 2021) [2]. Methodology: The following variables were used: housing prices, interest rates, mortality rates, and the consumer price index. The econometric testing simulates the possible paths of these variables, estimates the probability of occurrence of the paths, and calculates the expected losses of bidding banks. Findings: The results show that reverse mortgages are a good complement to Colombia’s pension system and confirm the feasibility of implementation at city level. It is recommended that the State stimulate the growth of this market and improve the corresponding regulatory framework. Originality: This study confirms the hypothesis that the reverse mortgages are a good complement to the pension system with city-level data. Specifically, it uses housing prices and mortality records from the main cities of the country (Bogot´a, Cali, and Medellín) to capture their idiosyncrasies.